2021
DOI: 10.1016/j.mad.2020.111413
|View full text |Cite
|
Sign up to set email alerts
|

Decreased serum levels of the inflammaging marker miR-146a are associated with clinical non-response to tocilizumab in COVID-19 patients

Abstract: Highlights Tocilizumab (TCZ) is currently being tested in COVID‐19‐induced cytokine storm. COVID-19 patients responding to TCZ have higher post-treatment levels of circulating miR-146a. Low levels of miR-146a are associated with death in COVID-19 patients not responding to TCZ. MicroRNAs can represent biomarkers of response to anti-inflammatory interventions in COVID-19.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
114
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(116 citation statements)
references
References 43 publications
2
114
0
Order By: Relevance
“…Among patients who did not respond to the treatment, the worst test results (the highest increase in plasma IL-6 concentration) occurred in those with the lowest serum miR-146a-5p levels. These data show that miR-146a-5p could serve as a biomarker and provide clues about the molecular relationship between inflammation and the clinical course of COVID-19 [237]. They concluded that blood biomarkers, such as miR-146a-5p, might represent a molecular relationship between inflammation and the clinical course of COVID-19 [237].…”
Section: Sensitivity and Specificity Of Microrna Profiling In Covid-19 Patientsmentioning
confidence: 72%
See 2 more Smart Citations
“…Among patients who did not respond to the treatment, the worst test results (the highest increase in plasma IL-6 concentration) occurred in those with the lowest serum miR-146a-5p levels. These data show that miR-146a-5p could serve as a biomarker and provide clues about the molecular relationship between inflammation and the clinical course of COVID-19 [237]. They concluded that blood biomarkers, such as miR-146a-5p, might represent a molecular relationship between inflammation and the clinical course of COVID-19 [237].…”
Section: Sensitivity and Specificity Of Microrna Profiling In Covid-19 Patientsmentioning
confidence: 72%
“…These data show that miR-146a-5p could serve as a biomarker and provide clues about the molecular relationship between inflammation and the clinical course of COVID-19 [237]. They concluded that blood biomarkers, such as miR-146a-5p, might represent a molecular relationship between inflammation and the clinical course of COVID-19 [237]. Sequencing the non-coding RNA and mRNA transcriptomes isolated from red blood cell-depleted whole blood of moderate to severe COVID-19 patients helped define four types of microRNAs with different expression trends that could serve as biomarkers of COVID-19 progression.…”
Section: Sensitivity and Specificity Of Microrna Profiling In Covid-19 Patientsmentioning
confidence: 76%
See 1 more Smart Citation
“…111 miR-146a-5p transcription is also regulated by NF-κB, 112 and patients with COVID-19 have been shown to have higher levels of IL-6 and lower levels of miR-146a-5p than average, suggesting imbalances in the physiological axis of IL-6/miR-146a-5p in the pathogenesis of COVID-19 infections. 113 TQ treatment, however, controls miR146a expression and can therefore reduce inflammatory reactions by interfering with NF-kB. 114…”
Section: Epigenetic Modulatory Effectmentioning
confidence: 99%
“…Several studies explored the interaction between miRNAs and SARS-CoV-2, which suggested potential therapeutic outcomes [ 19 ]. However, in COVID-19 patients with multifocal interstitial pneumonia, low serum levels of miRNAs related to the regulation of inflammation were associated with poor prognosis, high mortality rate, and subtherapeutic outcome [ 20 ]. On another note, miRNAs were explored in COVID-19 several organ complications.…”
Section: Introductionmentioning
confidence: 99%